Reduced graphene oxide on screen-printed carbon electrodes as biosensor for escherichia coli O157:H7 detection - Barthasarathy, Piravin Raj; Ahmed, Nasteho Ali; Wan Salim, Wan Wardatul Amani (MDPI, 2020)
Mixture of drinking-water supplies with sewage discharges poses disease threats in flood-stricken areas. In such exigent conditions, on-site testing of water samples is the only option, as water samples cannot be transported to laboratories owing to severely impacted transportation services. Hence, we developed a low-cost electrochemical biosensor fabricated from a screen-printed carbon electrode (SPCE) to detect E. coli O157:H7, a virulent pathogen often found in sewage discharges. We focused on understanding antigen-antibody interaction when the antibody used is not specific for E. coli O157:H7. We found that antibody immobilized on a reduced graphene oxide (rGO)–modified SPCEs distinguished between E. coli O157:H7 concentrations of 4 × 108 and 4 CFU/ml, with lowest current reported for 4 × 108 CFU/ml. In contrast, a reduced graphene oxide–modified SPCEs without antibody immobilization does not produce a prominent peak that distinguishes the highest and lowest E. coli concentrations. However, a few E. coli cells were still attached to the rGO/SPCEs in the absence of antibody, as shown in FESEM images. A processing step of differential readings from reference and active electrodes needs to be programmed into an Arduino® microprocessor to realize a prototype of a bacteria sensor for field use.